MiR-4463 inhibits the migration of human aortic smooth muscle cells by AMOT. Issue 5 (21st September 2018) - Wang, Xueqin; Du, Chao; He, Xuemei; Deng, Xian; He, Yanzheng; Zhou, Xiangyu
Abstract : Aberrant vascular smooth muscle cell (VSMC) migration has been implicated in a variety of vascular disorders, while the signal pathways governing this process remain unclear. Here, we investigated whether miRNAs, which are strong post-transcriptional regulators of gene expression, could alter VSMC migration. We detected the expression of miR-4463 in the plasma of patients with atherosclerosis and in human aortic smooth muscle cells under hypoxia–ischemia condition, and investigated the migration effect and its downstream pathways. The results have shown that whether in clinical AS patients or hypoxic cells, the expression of miR-4463 was lower than that of normal group, then the number of migrating cells in the miR-4463 mimic intervention group was significantly decreased compared with the normal group and miR-4463 inhibitor instead. Furthermore, the expression of angiomotin (AMOT) in gastrocnemius muscle and femoral artery of patients was significantly higher than that of the control group. The protein level of AMOT in miR-4463 mimic intervention group was significantly decreased, and its level was reversed by inhibiting miR-4463. In summary, these results indicate that miR-4463 is a novel modulator of VSMC migration by targetting AMOT expression. Regulating miR-4463 or its specific downstream target genes in VSMCs may represent an attractive approach for the treatment of vascular diseases.